An Efficient Strategy for Protecting Dihydroxyl Groups of Catechols - Huang, Wei-Bin; Guo, Ying; Jiang, Jian-An; Pan, Xian-Dao; Liao, Dao-Hua; Ji, Ya-Fei (Synlett, 2013)
A novel strategy for protecting dihydroxyl groups of catechols has been developed. Base-mediated cyclizations of catechols with 1,3-dibromopropane provided the corresponding benzo[b]1,4-dioxepans, and herefrom the protecting group was easily cleaved by aluminum chloride. The preparation of the antibacterial and antifungal agent 4-(2-aminothiazol-4-yl)benzene-1,2-diol from catechol reliably verified its availability amenable to various harsh reaction conditions.
Keywords: catechols; protection; ortho-dihydroxyl; 1,3-dibromopropane; benzo[b]1,4-dioxepans; deprotection; aluminum chloride